Fashioning of Students' Research Competence Through Technology of Project Activities - Khamzina, Sholpan S.; Utilova, Aigul M.; Shakenova, Tattigul Zh.; Suleimenova, Gulmira A.; Sarsembayeva, Ella Y.; Bobizoda, Gulomkodir Ðœ. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The authors provide justifications for changing the current education system, updating the teaching and methodological approach in school specialised education. The paper investigates the issue of fashioning students' research competence through the technology of project activities. Background: Project activity has become widely used since it combines the theoretical and practical parts of the science under study, which allows to set up a connection between its components. Research competence is an integral feature of a student's personality, which manifests itself in a willingness to take an active research position. Method: The authors conducted an experiment to study the problem of improving the quality of students' knowledge upon studying biology in senior school. The participants in the experiment were 120 students of the 10th and 11th years of a specialised school for children with psychological disorders. Results: The authors developed a methodology for the fashioning of research competence. The results of the conducted pedagogical experiment confirmed the validity of the initial assumptions regarding the influence of the use of research teaching methods in biology lessons aimed at improving the quality of biological education. Conclusion: Through project activities, students with intellectual disabilities learn to work in a team. Despite the fact that teamwork is uniting, each of the students learns to independently set the purpose and tasks of the study, analyse the sources presented, present the results of their activities to others. The main signs of project activity include the fact that students learn the technique and technology of working with the project. Project activity allows for the fashioning of students' research competence during the lesson, thereby enabling students to unleash their potential.